2018
DOI: 10.3934/publichealth.2018.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of levels of awareness towards blood donation in Saudi Arabia

Abstract: Backgroundblood products is an interesting term as all blood and blood transfusion procedures carry risk even with advance screening of donors and donated blood. In Saudi Arabia voluntary donors are either the only source or not, the other source is paid donors and the lack of volunteers represents a major challenge. This is usually attributed to low community awareness regarding voluntary blood donation. Therefore, the objective of this study was to assess the levels of awareness towards blood donation in nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Participants' knowledge regarding blood donation was found to be low, as they were not aware of the principles of blood donation. These results agree with national studies [7][8][9][10] and international studies conducted in Jordan [12] and Kuwait. [13] Alsalmi et al [11] in their study among health professions students in Saudi Arabia, concluded that the level of awareness was sufficient at 60% of study participants.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Participants' knowledge regarding blood donation was found to be low, as they were not aware of the principles of blood donation. These results agree with national studies [7][8][9][10] and international studies conducted in Jordan [12] and Kuwait. [13] Alsalmi et al [11] in their study among health professions students in Saudi Arabia, concluded that the level of awareness was sufficient at 60% of study participants.…”
Section: Discussionsupporting
confidence: 92%
“…Data were collected for the study using a predesigned structured questionnaire whose design was based on WHO guidelines and the relevant literature. [ 5 6 7 8 9 10 ] The self-administered questionnaire was distributed by the study team. The study team first visited the target colleges, identified the study participants, stated the study objectives, and distributed the questionnaires.…”
Section: S Ubjects and M Ethodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social media channels are becoming increasingly important for blood banks and transfusion services and appear to be a new tool in donor education and recruitment. While 7% of donors reported being attracted to donate blood by social media in Germany [12], social media was reported to be the main source by the public in Saudi Arabia, regardless of the educational level of the participants [13]. In our study, 93% of the participants are social media users who have seen an advertisement for blood donation on social media.…”
Section: Discussionmentioning
confidence: 58%